The Impact of Decline in Activities of Daily Living (ADL) of Patients With Critical Limb Ischemia (CLI) After Endovascular Treatment. (August 2018) - Tokuda, Takahiro; Hirano, Keisuke; Yamawaki, Masahiro; Araki, Motoharu; Kobayashi, Norihiro; Sakamoto, Yasunari; Mori, Shisuke; Tsutsumi, Masakazu; Honda, Yosuke; Ito, Yoshiaki
Background: Certain patients with critical limb ischemia (CLI) experience significant decline in activities of daily living (ADL) during hospitalization. The prognosis of decline in ADL during hospitalization remains unknown. Methods: A retrospective analysis was performed on collected data of patients with CLI treated by endovascular treatment between April 2007 and December 2015. We evaluated CLI in patients ADL at the time of hospitalization and after discharge using the Barthel index. We classified all patients into patients with decline in ADL and stable in ADL and compared clinical outcomes (cumulative incidence of wound healing, amputation-free survival at 1 year) between the 2 groups. Results: Two hundred and fifty-five consecutive patients with CLI (221 limbs), who underwent successful endovascular intervention, were enrolled in this study. Of all patients, 22 patients were classified into the decline group. The prevalence of wound, Ischemia, foot infection (WIfI) classification high grade was higher in the decline group (30.7% vs 63.6%; P < .01). The wound healing rates were worse in the decline group than in the stable group (40% vs 78% at 1 year; P < .01). The same trends were observed in the amputation-free survival (37% vs 78%; P < .01). After multivariate analysis, decline in ADL was an independent predictor of wound healing and amputation-free survival (odds ratio [OR]: 2.85, 95% confidence interval [CI]: 1.61-3.35, P < .01; OR: 2.46, 95% CI: 1.26-4.53, P = .01). Conclusions: Patients with CLI with decline in ADL during hospitalization were found to have a poor prognosis suggesting that a decline in ADL may affect the clinical outcomes.